2022
DOI: 10.1186/s13049-022-00994-7
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from the first 50 COVID-19 critical care transfer missions conducted by a civilian UK Helicopter Emergency Medical Service team

Abstract: Background The COVID-19 pandemic has placed exceptional demand on Intensive Care Units, necessitating the critical care transfer of patients on a regional and national scale. Performing these transfers required specialist expertise and involved moving patients over significant distances. Air Ambulance Kent Surrey Sussex created a designated critical care transfer team and was one of the first civilian air ambulances in the United Kingdom to move ventilated COVID-19 patients by air. We describe … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The SARS-CoV-2 pandemic caused congestion in health care systems across Europe, and alternative transportation options were developed to relieve regional hospitals (i.e. ambulance bus in the Netherlands 28 or transport by civilian helicopter emergency medical service (HEMS, UK) 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The SARS-CoV-2 pandemic caused congestion in health care systems across Europe, and alternative transportation options were developed to relieve regional hospitals (i.e. ambulance bus in the Netherlands 28 or transport by civilian helicopter emergency medical service (HEMS, UK) 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Capacity transfers, previously termed ‘non‐clinical’, have long been presumed to be associated with risk and harm [ 9 ] as well as being used as a metric of an underperforming critical care unit or system [ 10 ]. The reasons for this are multiple, but it was accepted they would only occur when a critical care unit was under extreme pressure or unable to cope with the case‐load it faced.…”
Section: Critical Care Transfers For Capacitymentioning
confidence: 99%
“…The paper by Huq et al. [ 8 ] is one of a series from around the world [ 9 , 10 , 11 ] which have variably assessed the efficacy, physiological effects and outcomes of patients requiring critical care transfer during the pandemic. Evidence published before 2020 has long suggested that critical care transfer can be carried out safely by dedicated transfer and retrieval teams [ 1 ], with the best evidence from countries with well‐developed systems such as Australia.…”
Section: What Is the Current Evidence Base?mentioning
confidence: 99%
“…Evidence on acute hospital transfers during the pandemic has been limited to local or narrative reports, surveys, specific patient cohorts (eg, those with stroke or ST-elevation myocardial infarction), and non-US studies. 6,[12][13][14][15][16][17] Most US states have not reported their experience with transfers to date, and among the few that have, the ability to transfer patients appeared to vary substantially across individual US state-based transfer coordination enters. 17,18 Furthermore, there were media reports of US hospitals making multiple unsuccessful attempts to move patients to other hospitals.…”
Section: Introductionmentioning
confidence: 99%